The Financial Position of the Top Accountancy Firms in the UK - Rompotis, Gerasimos (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The consolidated financial position of the Top 6 accountancy companies in the UK is the subject of this paper. Top 6 include PwC, Deloitte, EY, KPMG, BDO and Grant Thornton. The study period spans from 2014 to 2024. Key figures from the group balance sheet and the profit and loss statement and their growth over the study period are examined. The structure of the balance sheet is evaluated too. Next, liquidity, leverage and performance financial ratios are computed. The impact of the Covid-19 health crisis on financial performance is assessed too. Furthermore, a comparative panel regression analysis of financial performance among the sample firms is applied. Finally, regression analysis on the determinative factors of performance is conducted. The results show that the Top 6 accountancy firms in the UK are quite liquid and profitable, whereas they are financed via external capital and to a lesser degree via equity. The majority of the financial performance metrics computed along with the metric of firms’ ability to leverage their assets to make revenue are impressive. On the question of the coronavirus’ impact on financial position, the results show that the revenue and profitability of the Big 6 in the UK have been significantly higher during the post-covid era. However, the financial performance measures have not. Finally, the econometric analysis reveals a negative correlation between size and financial performance, while a positive relationship of financial performance is accentuated with the debt-to-equity ratio, the cash ratio, the efficiency ratio, and the revenue per employee.